Software development for transformer health assessment - Maria Sonia Michael (2023)
This project entitled Software Development for Transformer Health Assessment is intended to provide a feasible solution to this problem. In conjunction, this project presents an effective Health Index Model which is a calculation structure involving various test parameters carrying specific weightages to deduce the overall health of power transformers. Proper weighting of each test result to reflect the reality of transformer degradation and failure modes were critically analysed and deduced based on relevant standards in practice. The model presented in this project was formulated through detailed study and comprehensive discussions with experienced engineers and is verified to be in compliance with the relevant standards. This project also presents an efficient and reliable software that computes the Health Index and evaluates power transformer condition.